Mathematical Modelling of the Growth of Yeast Candida tropicalis TL-F1 on Azo Dyes (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
Azo dyes are the most common chemical family of dyes, with a wide range of structural and color variations. They account for up to 70% of yearly dye production. Azo dyes are one of the first man-made compounds, and they are still commonly used in the food and textile industries. The discharge of Azo dyes is undesirable not only because many Azo dyes and their breakdown products are toxic to aquatic life and mutagenic to people, but also because many Azo dyes and their breakdown products are harmful to aquatic life and mutagenic to humans. We report different primary kinetics models such as Huang, modified Gompertz, Buchanan-3-phase, modified Logistics, Baranyi-Roberts, modified Richards and Von Bertalanffy were used to get the best model for Candida tropicalis TL-F1 growth on different Azo dyes concentrations. The best model was found to be Buchanan-3-phase with the lowest values for AICc, RMSE and the highest value for adjusted R2. The AF and BF values were also excellent for the model with their values were the closest to 1.0. The poorest performance was found to be Baranyi-Roberts where it failed to model the growth curve. Baranyi-Roberts has the highest values for AICc, RMSE and the highest value for adjusted R2. The Buchanan-3-phase parameters such as Y0, Î», k and Ymax were found to be 0.290, 3.244, 0.543 and 3.825 respectively. These constant would provide insight for the actual Candida tropicalis TL-F1 growth curve.
Keywords: Buchanan-3-phase; Azo dye; modelling; kinetics; Candida tropicalis TL-F1